Convolutional Neural Network for Solid Waste Segregation and Management - Tze Chin Ong, Mun Geet Ow Yong,Norhoneydayati Abdul Manap,Farhah Abdullah,Tze San Ong (International Journal of Advanced Science and Technology, 2020)
E-commerce creates its own borderless market with advance technologies and availability of vast information, which generated significant harms to consumers. The technologies driven, borderless context of e-commerce seems to create a prefect competition of market structure. In fact, e-commerce that creates its own market and regulates its own game is an anti-competition practices, which directly interfere with domestic market. E-commerce markets obtain strong economies of scale and scope in order to provide low marginal cost and in returns for data provided by consumers. E-commerce has disrupt the market equilibrium creating segregate wide margin of producer and consumer surplus directly affecting consumers economic and welfare. In many instances, data provided by consumers were sold for other purposes without the knowledge of consumers. The issue of e-commerce platforms that is capable of exploit their market power to increase profits and for its own gain is of alarming issues in encouraging a fair competitive market. This paper provide analysis of e-commerce market power of consumer sale of goods in the context of competition perspective in Malaysia. Qualitative research by employing content analysis, this paper aims to analyses the market power of e-commerce consumer sale of goods and the issues arising in the technologies driven market structure for a deeper understanding of competition perspective in Malaysia